Phylogeny and Species Delimitation of Chinese Medicago (Leguminosae) and Its Relatives Based on Molecular and Morphological Evidence - Chen, Jinyuan; Wu, Guili; Shrestha, Nawal; Wu, Shuang; Guo, Wei; Yin, Mou; Li, Ao; Liu, Jianquan; Ren, Guangpeng (Frontiers in Plant Science, 2021)
Medicago and its relatives, Trigonella and Melilotus comprise the most important forage resources globally. The alfalfa selected from the wild relatives has been cultivated worldwide as the forage queen. In the Flora of China, 15 Medicago, eight Trigonella and four Melilotus species are recorded, of which six Medicago and two Trigonella species are introduced. Although several studies have been conducted to investigate the phylogenetic relationship within the three genera, many Chinese naturally distributed or endemic species are not included in those studies. Therefore, the taxonomic identity and phylogenetic relationship of these species remains unclear. In this study, we collected samples representing 18 out of 19 Chinese naturally distributed species of these three genera and three introduced Medicago species, and applied an integrative approach by combining evidences from population-based morphological clusters and molecular data to investigate species boundaries. A total of 186 individuals selected from 156 populations and 454 individuals from 124 populations were collected for genetic and morphological analyses, respectively. We sequenced three commonly used DNA barcodes (trnH-psbA, trnK-matK and ITS) and one nuclear marker (GA3ox1) for phylogenetic analyses. We found that 16 out of 21 species could be well delimited based on phylogenetic analyses and morphological clusters. Two Trigonella species may be merged as one species or treated as two subspecies, and M. falcata should be treated as a subspecies of the M. sativa complex. We further found that major incongruences between the chloroplast and nuclear trees mainly occurred among the deep diverging lineages, which may be resulted from hybridization, incomplete lineage sorting and/or sampling errors. Further studies involving a finer sampling of species associated with large scale genomic data should be employed to better understand the species delimitation of these three genera.